ANALISIS TINGKAT KEPUASAN PELANGGAN DENGAN MENGGUNAKAN METODE CUSTOMER SATISFACTION INDEX DAN IMPORTANCE PERFORMANCE ANALYSISSERTA SERVICE QUALITY - Arie Pohandry; Muhammad Yusuf; Winarni (Jurusan Teknik Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2013)
88DB Indonesia Yogyakarta branch difficulty to obtain new customers and retain existing customers. New customers as the target PT. 88DB Indonesia Yogyakarta branch refusing offers of services provided and the old customers make complaints and termination of the contract. PT.88DB Indonesia Yogyakarta branch should evaluate the level of customer satisfaction of services provided. This study uses a Customer Satisfaction Index to measure the overall level of customer satisfaction. Then proceed with the measure by using Importance Performance Analysis to determine the attributes that have not been satisfying the customers. To sort the attributes do not satisfy the customer satisfaction levels by measuring the difference in performance levels using Service Quality. Results of this study showed that the majority of customers are satisfied with the services provided but not maximum yet. It can be seen from the results of customer satisfaction level testing using Customer Satisfaction Index (CSI) which is equal to 67.93%. On testing using the Importance Performance Analysist (IPA), there are 9 service attributes that go into quadrant I, which means that there are 9 attributes that unsatisfactory customers and the service is not maximum yet. Based on testing using the Service Quality attributes improvements sequence starting from the attribute number 4 (SEO optimazed pages) because it has the greatest negative value.